2019
DOI: 10.1039/c9ra01988j
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for textile odor removal using engineered water nanostructures

Abstract: The malodor attached to textiles not only causes indoor environmental pollution but also endangers people's health even at low concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…To date, there are few published papers employing the ISO method. [36][37][38][39] Lee et al 36,37 used the gas detector method to evaluate the deodorizing properties of natural dyes and mordants used on cotton, silk, and wool fabrics with ammonia and acetic acid as challenge odorants. No correlation of odor reduction rates with sensory panels was conducted.…”
Section: Collection Of Odor On Textilesmentioning
confidence: 99%
“…To date, there are few published papers employing the ISO method. [36][37][38][39] Lee et al 36,37 used the gas detector method to evaluate the deodorizing properties of natural dyes and mordants used on cotton, silk, and wool fabrics with ammonia and acetic acid as challenge odorants. No correlation of odor reduction rates with sensory panels was conducted.…”
Section: Collection Of Odor On Textilesmentioning
confidence: 99%
“…Zhu has Engineered Water Nanostructures (EWNS) that take advantage of the Reactive Oxygen Species (ROS, which are made up of hydroxyl and superoxide radicals), to remove odors produced by smoking, cooking, and sweating. 23 Current studies have not systematically considered the effects of these factors on the desorption of odor compounds from fabrics. 14 The literature review showed that an odor deposition and desorption dynamic model and analysis of the fibrous porous media are still unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…There is an ever growing demand for specialty textile with one specific or multiple functions. Indeed, much has been achieved recently in this domain, namely textiles with odour elimination property ; Zhu et al, 2019), textiles for tissue engineering (Augustine et al, 2017) and wound healing (Kim, Cha and Gong, 2018), specialty textiles for military applications (Revaiah, Kotresh and Kandasubramanian, 2019), textiles for wearable electronics (Zhou et al, 2019), or catalytic applications (Fujii and Nakamura, 2013). Either woven or non-woven, cotton fibers remain the most used for clothing or specialty textiles due to the biodegradability, strong absorption capacity and porosity of these cellulosic fibers.…”
Section: Introductionmentioning
confidence: 99%